Antimicrobial effect of the essential oil of oregano against Listeria monocytogenes and Staphylococcus aureus - Carhuallanqui Pérez, Andrea (2020)
The food industry uses chemical compounds to prevent the growth of bacteria and extend their shelf life. These substances are associated with toxic problems, the presence of chemical residues and antimicrobial resistance. Oregano essential oil has antimicrobial compounds such as thymol and carvacrol. The objective of the research was to evaluate the antimicrobial effect of oregano essential oil from the province of Concepción, Junín Region (Peru) against Listeria monocytogenes and Staphylococcus aureus. Oregano was taxonomically identified as O. vulgare. The essential oil was obtained by hydrodistillation and the profile of chemical compounds was determined by Gas Chromatography/Mass Spectrometry (GC-MS). The minimum inhibitory concentration (MIC) was determined by microdilution and the minimum bactericidal concentration (CMB) by agar planting Baird-Parker Agar was used for S. aureus and for L. monocytogenes the DNA hybridization method was used using the Gene Quencekit® L. monocytogenes. The GC-MS profile of oregano oil had 11.9% thymol and 1.7% carvacrol. The oil exhibited antimicrobial activity against S. aureus (CMI 2%, CMB 4%) and L. monocytogenes (CMI-4%, CMB-4%). The high percentage of CMI and CMB was due to the low concentration of carvacrol and thymol, however this oil can be used in the food industry as a natural antimicrobial and/or disinfectant.